MODERN COMMUNICATIONS TECHNOLOGIES AND THEIR ROLE IN IMPROVING AGRICULTUAL EXTENSION WORK IN MIDDLE IRAQE GOVERNORATES - & Salman, Abdul-Razzaq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The aim of this research to study the role of modern communication technologies in improving agricultural extension work in middle Iraqi governorates by providing infrastructure to use modern communication technologies in Agricultural extension work , support agricultural extension system to transform agricultural work to electronic government , electronic management of human resources , extension services introduced for the targeted people through internet  and the contribution of modern communication technologies in improving agricultural work .The population of the research includes the middle region governorates numbered (8) governorates .Anbar and Tikret were excluded because of the security conditions in the time of data collection .Thus, the research society becomes (6) governorates .A random sample was taken from  the governorates (67%) rate from (4) governorates  ( Baghdad, Karbala , Babel , Dyala) .A random  sample was taken in rate (40%) from agricultural extension agents distributed  on the above mentioned governorates who numbered ( 135) out of (335) agricultural extension agents .  In order to achieve the research objectives a questionnaire form designed to collect the data from agricultural extension agents .It includes (49) items in the field of modern communication technologies role .To analyses and introduce the results (SPSS) program used as well as the manual analyses .The following statistical methods were used : the frequencies , percentages , weighted average , weight percentage as well as (SPSS) program to measure Cronbach Coefficient .The results showed that if these technologies are available sufficiently it would lead to achieve the objectives .Also, the modern communication technologies are considered the widely applied methods in agricultural extension work .Also, there is agreement by the agricultural extension agents on the necessity of using modern communication technologies to develop agricultural extension work .Also, there is support from the agricultural extension system to transform agricultural  extension work from traditional work to electronic government . This research concludes the necessity of providing modern technologies in all extension directories , centers , offices and farms in order to improve agriculture extension work in Iraq .Also, it recommends to establish wide information base related to extension work  .Also, it recommends to invoke extension management to support the plans to modernize the communications methods that are used in extension work which fulfill the treatment of the huge amounts of available information for the agricultural extension product as well as making the necessary plans to rehabilitate and train the workers  in the agricultural extension system to transform the traditional extension work to electronic government .